Comparison of QuantiFERON-TB Gold Plus and QuantiFERON-TB Gold In-Tube tests for patients with active and latent tuberculosis: A prospective cohort study. Issue 12 (December 2021) - Lee, Jung-Kyu; Lee, Hyun Woo; Heo, Eun Young; Yim, Jae-Joon; Kim, Deog Kyeom
Abstract: Introduction: We aimed to determine the diagnostic performance and clinical value of the QuantiFERON-TB Gold In-Tube (QFT-GIT) and QuantiFERON-TB Gold Plus (QFT-Plus) tests in patients with active tuberculosis (TB) or latent TB infection (LTBI). Methods: We prospectively enrolled 140 patients, including 63 with active TB and 77 with LTBI, between March 2017 and October 2018. QFT-GIT and QFT-Plus were performed simultaneously in all subjects. Results: QFT-Plus and QFT-GIT test results showed significant agreement, in both active TB and LTBI patients, in terms of the interferon-γ concentration and interpretation result. QFT-Plus had higher sensitivity than QFT-GIT for predicting active TB (82.5% vs. 77.8%) and showed fewer false-negative and indeterminate results in both active TB and LTBI patients due to its "TB2 tube". The QFT-Plus TB2-TB1 value was higher in the active TB group than in the LTBI group. The QFT-Plus TB1-Nil and TB2-Nil values were useful in predicting remote LTBI, rather than recent LTBI. Conclusions: QFT-Plus showed good agreement with QFT-GIT in both active TB and LTBI patients, and higher sensitivity for predicting active TB than QFT-GIT. The QFT-Plus TB2 tube results, which reflect CD8 + T cell immunity, may improve predictive accuracy and detection of the immune response associated with active TB and LTBI.